Embolic obstruction of the tibio-peroneal trunk and of the tibialis anterior postarteriography with Seldinger catheter: Remote treatment with vein graft - Danza, Rómulo; Galarraga, José; Arias, José; Olivera, Daniel (Cirugía del Uruguay, 1975)
The authors report a case of embolic obslruction of the tibial-peroneal trunk, following the introduction of a Seldinger's catheter in a healthy femoral artery, in order to study cerebral circulation. The patient, after a severe acute ischemia, was able to preserve the trophism of his limb, although with severe intermitent claudication. An arteriographic study showed complete obstruction of the tibial-peroneal trunk and of the anterior tibial artery in its origin. The treatment consisted on a free graft, uslng the great saphenous vein, from the lower end of the popliteal artery up to the posterior tibia! artery in the middle of the calf, with excellent clinical and arteriographic results.